Non-invasive diagnosis and assessment of aortic valve disease and evaluation of aortic prosthesis function using echo pulsed Doppler velocimetry. - Veyrat, C (1980)
Non-invasive recording of aortic blood flow velocity patterns in the ascending aorta and in the arch of the aorta was performed in 12 normal subjects, 38 patients with confirmed aortic valve disease, and 13 patients with aortic prostheses using pulse echo Doppler velocity recordings. In normal subjects, the velocity recordings correlated well with those obtained by other authors using invasive procedures. In patients with aortic valve disease, specific abnormalities of the velocity curves were found to correlate well both with the type of lesion (stenosis or regurgitation) and its severity on a three-point scale. Both sensitivity and specificity were found to range between 80 and 94 per cent. A less accurate grading of severity was obtained from patients with aortic regurgitation by the detection of turbulence in the left ventricular outflow tract than from the appearance of the aortic velocity curves. In the studies of patients with aortic prostheses, anomalies of the velocity pattern could be found in the ascending aorta in 53 per cent but no abnormalities of timing was found. In spite of some technical limitations, pulse echo Doppler velocity recordings provide a new non-invasive, reliable, and reproducible approach in assessing the presence and severity of aortic lesions and demonstrating flow abnormalities produced by prostheses.